Preparation of intelligent self-repairing iron-nickel-based corrosion-resistant alloy material

By preparing intelligent self-healing iron-nickel-based corrosion-resistant alloy materials, combined with acrylic resin, microcapsules, magnesium alloys and electrodeposited iron-nickel alloys, the design and preparation of the material's corrosion resistance, self-healing and intelligent functions are solved. , realizes efficient, economical and environmentally friendly material preparation, suitable for medical equipment and other fields.

CN119506990APending Publication Date: 2025-02-25HEYE HEALTH TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411691762.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When preparing intelligent self-healing iron-nickel-based corrosion-resistant alloy materials, it is necessary to solve the problems of material design and preparation, performance optimization and improvement, as well as cost control and reduction, so as to achieve excellent corrosion resistance, self-healing and intelligent functions.

Method used

Through the synthesis of acrylic resin, the preparation of microcapsules, the pretreatment of magnesium alloy substrates, the preparation of electrodeposited iron-nickel alloys, and the preparation of precursor ceramic repair agents, combined with heat treatment technology, intelligent self-repairing iron-nickel-based corrosion resistance was prepared. Alloy material.

Benefits of technology

It realizes the high corrosion resistance, self-repair capability and intelligent functions of the material, extends the service life of medical equipment, improves the reliability and safety of the equipment, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506990A_ABST
    Figure CN119506990A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material, which comprises the following steps: synthesis of acrylic resin, preparation process of microcapsules, pretreatment of a magnesium alloy substrate, preparation of an acrylic resin coating, preparation of an electro-deposition iron-nickel alloy, preparation of a precursor ceramic repairing agent, and preparation of the intelligent self-repairing iron-nickel-based corrosion-resistant alloy material. An electrodeposition method, a solution polymerization method and a coating preparation method are creatively combined, the prepared intelligent self-repairing iron-nickel-based corrosion-resistant alloy material is a high-strength and high-hardness alloy material, and the intelligent self-repairing iron-nickel-based corrosion-resistant alloy material has the advantages of self-repairing function, corrosion resistance, wear resistance and high hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of an intelligent self-repairing iron-nickel based corrosion resistant alloy material, and belongs to the field of new material preparation. Background Art

[0002] As an important soft magnetic material and functional material, iron-nickel alloy has a wide range of applications in high-tech fields such as biomedicine and intelligent control. Its excellent soft magnetic properties and mechanical properties make it one of the ideal materials for the preparation of medical equipment. The corrosion resistance, biocompatibility and machinability of iron-nickel alloy provide a basis for the preparation of intelligent self-healing medical materials.

[0003] Nickel-based corrosion-resistant alloys are a type of alloy that uses nickel as a matrix and is corrosion-resistant in some media. This type of alloy can obtain excellent corrosion resistance by adding different elements and using specific preparation processes. Self-healing materials are materials that can automatically detect and repair damage. Self-healing materials can extend the service life of medical equipment and improve the reliability and safety of equipment. The following challenges need to be addressed when preparing intelligent self-healing iron-nickel-based corrosion-resistant alloy materials. Material design and preparation: How to design and prepare iron-nickel-based alloy materials with excellent corrosion resistance, self-healing and intelligent functions; Performance optimization and improvement: How to improve the comprehensive performance of materials, such as corrosion resistance, mechanical strength, biocompatibility, etc.; Cost control and reduction: How to reduce the preparation cost of materials to make them more competitive in the market. The preparation of intelligent self-healing iron-nickel-based corrosion-resistant alloy materials also brings the following opportunities. Expanding application areas: It can be applied to more medical devices, such as pacemakers, artificial joints, etc.; Improving the performance of medical equipment: By improving the performance of materials, the service life of medical equipment can be extended, and the reliability and safety of equipment can be improved; Promoting scientific and technological progress: Promoting scientific and technological progress and development in the fields of materials science and biomedicine. Summary of the invention

[0004] In view of the above problems, the present invention provides an intelligent self-repairing iron-nickel based corrosion-resistant alloy material.

[0005] The present invention provides an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material, comprising the following steps: step (1) synthesis of acrylic resin, step (2) preparation process of microcapsules, step (3) pretreatment of magnesium alloy substrate, step (4) preparation of acrylic resin coating, step (5) preparation of electrodeposited iron-nickel alloy, step (6) preparation of precursor ceramic repair agent, and step (7) preparation of intelligent self-repairing iron-nickel-based corrosion-resistant alloy material; Wherein, the preparation of the precursor ceramic repair agent in step (6) comprises: PMHS (polymethyl hydrogen siloxane) and D4Vi solution (acrylate copolymer emulsion) were weighed, mixed and magnetically stirred to fully mix the two phases of the solution to obtain the matrix of the precursor ceramic repair agent; on the basis of the precursor repair agent matrix, nano-TiB 2 The filler is added into the repair agent matrix solution, and stirring is continued to make the polymer repair material and the filler completely mixed and uniform to obtain a precursor ceramic repair agent; Step (7) The intelligent self-repairing iron-nickel based corrosion resistant alloy material comprises: The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are heat-treated by a two-step heat preservation method, and then the electrodeposited iron-nickel alloy prepared in step (5) is added, and the temperature is increased in an air environment and then kept warm to accelerate the curing process. The completely cured material is heated and kept warm to fully pyrolyze it, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0006] Preferably, in step (1), the synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the polymerization inhibitor, then add initiator 1 (dibenzoyl peroxide and dibutyl phthalate) to mix; take the mixed solution and butyl acetate and mix them into a four-necked flask, then add itaconic acid and a molecular weight regulator (3-mercaptopropionate); put the remaining mixed solution into a micro pump for standby use; stir under heating and reflux conditions, start to drop the mixed solution and add itaconic acid during the dropping process; after the dropping is completed, keep warm; Step (2) Preparation of microcapsules Soak polyvinyl alcohol in deionized water and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature; finally obtain a stable acrylic resin emulsion, which is milky white in color; dilute hydrochloric acid with deionized water, acidify aniline to a certain pH range, and drop the acidified aniline into the acrylic resin emulsion to react, thereby obtaining a light yellow prepolymer emulsion; at the same time, slowly and continuously drop the acidified aniline and initiator 2 (ammonium persulfate) aqueous solution into a four-necked flask until the addition is complete; first use sodium chloride to break the emulsion, add deionized water and use a filter membrane to filter, wash until the pH is neutral, disperse in anhydrous ethanol, filter with gauze, and remove the lower layer; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy, whose main components are: Mg, Al, Si, Ca, Zn, Mn, Cu, Ni; the magnesium alloy substrate is polished in one direction with sandpaper, then cleaned with deionized water and anhydrous ethanol and blown dry for standby use, cleaned with anhydrous ethanol, and blown dry with cold air to obtain the magnesium alloy substrate; Step (4) Preparation of acrylic resin coating Adding acrylic resin to epoxy resin (E-44) and stirring evenly, then adding epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stirring, coating on the AZ31B magnesium alloy treated in step (3) after fully ripening, and curing at room temperature to obtain an acrylic resin coating; Step (5) Preparation of Electrodeposited Iron-Nickel Alloy Nickel sulfate, ferrous sulfate, sodium chloride, boric acid, sodium citrate, saccharin, and sodium benzenesulfite are placed in different beakers, dissolved in deionized water, and poured into an electric forging tank, stirred evenly, and a circulating water pump is started. The solution is stirred to ensure the uniformity of the plating solution, and a constant temperature water bath is started. The temperature is observed by a thermometer, the current density is adjusted, the electrodes are fixed, and the power is started to start electrodeposition on the copper foil. At the same time, ferrous sulfate is continuously added to ensure the ion ratio in the solution and the electroplating time is controlled; the power is turned off and the electrodeposited sample is taken out; the electrodeposited surface is rinsed with deionized water and blown dry with a hot air blower; Step (6) Preparation of precursor ceramic repair agent PMHS (polymethyl hydrogen siloxane) and D4Vi solution (acrylate copolymer emulsion) were weighed, mixed and magnetically stirred to fully mix the two phases of the solution to obtain the matrix of the precursor ceramic repair agent; on the basis of the precursor repair agent matrix, nano-TiB 2 The filler is added into the repair agent matrix solution, and stirring is continued to make the polymer repair material and the filler completely mixed and uniform to obtain a precursor ceramic repair agent; Step (7) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish, and heat-treated by a two-step heat preservation method. Then, the electrodeposited iron-nickel alloy prepared in step (5) is added, and the temperature is increased in an air environment and then kept warm to accelerate the curing process. The completely cured material is placed in a muffle furnace, heated and kept warm to fully pyrolyze it, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0007] Preferably, in step (1), the synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the inhibitor, then add 1.0-1.5g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 15-20% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.0-6.4g of itaconic acid and 4.0-4.5g of molecular weight regulator (3-isooctyl mercaptopropionate); the remaining 75-80% of the mixed solution is put into a micro pump for standby use; heat to 100-126°C, stir for 0.3-0.5h under reflux condition, start to drip the remaining 75-80% of the mixed solution (drip in 2-8h) and add 3.0-3.5g of itaconic acid every 0.5-1.0h during the dripping process; after the dripping is completed, keep warm for 1-2h.

[0008] The invention has the advantages that butyl acetate is used as a solvent to dissolve the mixed monomers and promote the polymerization reaction; the conditions of the polymerization reaction can be accurately controlled by accurately dropping the mixed solution and adding itaconic acid at regular intervals through a micro pump, thereby obtaining an acrylic resin with specific properties; stirring and dropping operations are performed under reflux conditions, which is beneficial to promoting the mixing and reaction of reactants and improving the efficiency of the polymerization reaction.

[0009] Preferably, in step (2), the preparation of microcapsules Soak polyvinyl alcohol and deionized water for 12-24 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 70-85°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 40-45 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; dilute hydrochloric acid with deionized water, and add aniline acid to pH 1-2; add 5-10% of acidified aniline to the acrylic resin emulsion and react for 1-3h; obtain a light yellow prepolymer emulsion; at the same time, slowly and continuously add the remaining 90-95% of acidified aniline and initiator 2 (ammonium persulfate) aqueous solution to the four-necked flask, and react for 10-12h after the addition is complete; first use sodium chloride to break the emulsion, add deionized water and filter with a 0.40-0.45μm filter membrane, wash until the pH is neutral, disperse in anhydrous ethanol, filter with 450-500 mesh gauze, and remove the lower layer.

[0010] The invention has the advantages that polyvinyl alcohol fully absorbs water and swells, fully dissolves in water, and forms a uniform solution; the microcapsules prepared by the method have uniform wall material and core material distribution, moderate wall material thickness, high mechanical strength, can effectively protect the core material and control its release, are suitable for the preparation of various core materials and wall materials, and the prepared microcapsules have the advantages of excellent performance, wide application range, environmental protection, energy saving, etc.

[0011] Preferably, in step (3), pretreatment of the magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy with a size of 45-50mm×45-50mm×3-5mm, and its main components (wt.%) are: Mg, Al 2.5-3.5, Si 0.05-0.09, Ca 0.03-0.05, Zn 0.6-1.4, Mn 0.2-1.0, Cu 0.01-0.03, Ni0.001-0.004; the magnesium alloy substrate is polished in one direction with 150-180 mesh and 400-450 mesh sandpaper in turn, and then cleaned with deionized water and anhydrous ethanol and blown dry for use, and the tinplate sheet with a size of 65-68mm×145-150mm×0.45-0.55mm is cleaned with anhydrous ethanol and blown dry with cold air to obtain the magnesium alloy substrate.

[0012] The advantage of adopting the present invention is that the sandpaper performs unidirectional grinding on the magnesium alloy substrate, which is beneficial to removing the oxide layer, dirt and uneven parts on the surface of the substrate, making the surface smoother and more uniform, and significantly improving the surface quality of the magnesium alloy substrate. The clean surface is beneficial to the close bonding between the coating or treatment layer and the substrate, thereby improving the overall mechanical properties and durability.

[0013] Preferably, in step (4), the preparation of the acrylic resin coating Add 2.0-3.5% of acrylic resin to the epoxy resin (E-44) and stir evenly, then add epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stir, and after fully ripening, apply it on the AZ31B magnesium alloy treated in step (3), and cure it at room temperature for 40-48 hours and at 50-55°C for 12-48 hours to obtain an acrylic resin coating.

[0014] The advantage of adopting the present invention is that by mixing acrylic resin with epoxy resin, n-butanol and xylene are used as solvents to facilitate the dissolution and coating of the resin, and their advantages can be fully utilized to improve the hardness, wear resistance, corrosion resistance and adhesion of the coating; the addition of microcapsules provides the coating with additional functions, such as self-repairing ability, etc.

[0015] Preferably, step (5) is to prepare an iron-nickel alloy by electrodeposition Place 20-120g / L nickel sulfate, 15-20g / L ferrous sulfate, 25-30g / L sodium chloride, 35-45g / L boric acid, 15-22g / L sodium citrate, 1-4g / L saccharin, and 0.2-0.5g / L sodium benzene sulfite in different beakers, dissolve them in deionized water, and pour them into the electric forging tank, stir evenly, start the circulating water pump, stir the solution at the same time to ensure the uniformity of the plating solution, start the constant temperature water bath, observe the temperature through the thermometer, and ensure that the plating solution temperature is controlled at 55-60°C; adjust 1-8A / dm2 Pulse current density, fix the electrode, start the power supply to start electrodeposition on the copper foil, and continuously add ferrous sulfate to ensure that Ni in the solution 2+ :Fe 2 + ion ratio, the electroplating time is controlled to be 25-30min; turn off the power and take out the electrodeposited sample; rinse the electrodeposited surface with deionized water and blow dry with a hot air blower.

[0016] The invention has the advantages that a constant temperature water bath and a circulating water pump are used to ensure that the temperature of the plating solution is uniform and stable, thereby improving the stability and repeatability of the electrodeposition process; the iron-nickel alloy coating prepared by electrodeposition has the advantages of good uniformity, low porosity, high density, etc., and deionized water is used as a solvent, thereby reducing the emission of harmful substances, reducing energy consumption, and improving production efficiency.

[0017] Preferably, in step (6), the preparation of the precursor ceramic repair agent Weigh PMHS and D4Vi solutions, mix them and stir them magnetically at 20-25°C for 20-25 minutes to fully mix the two phases of the solution to obtain the matrix of the precursor ceramic repair agent; on the basis of the precursor repair agent matrix, weigh nano-TiB 2 The filler is added into the repair agent matrix solution, and magnetic stirring is continued for 30-35 minutes at 24-30° C. to completely mix the polymer repair material and the filler to obtain a precursor ceramic repair agent.

[0018] The invention has the advantage that by controlling the PMHS and D4Vi solutions and stirring conditions, a precursor ceramic repair agent matrix with specific properties can be prepared, nano-TiB 2 The addition of fillers can significantly improve the hardness, wear resistance and chemical stability of the repair agent, making it more suitable for repair work in various harsh environments.

[0019] As a preferred method, step (7) intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish, and heat-treated by a two-step heat preservation method. Then, the electrodeposited iron-nickel alloy prepared in step (5) is added, and the alloy is heated to 250-350°C at a heating rate of 3-6°C / min in an air environment, and then kept warm for 55-60 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace, and heated to 850-900°C at a heating rate of 1-5°C / min and kept warm for 60-65 minutes to fully pyrolyze the alloy, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0020] The advantage of adopting the present invention is that the acrylic resin coating provides a basic protective layer for the alloy material, while the repair agent gives the material the ability to self-repair. Heat treatment helps to accelerate the curing process of the acrylic resin coating and make the coating more stable. High-temperature heat treatment allows the repair agent to fully pyrolyze and interact with the electrodeposited iron-nickel alloy to form a corrosion-resistant alloy layer with intelligent self-repair function. When the surface of the material is damaged, the repair agent can respond and repair the damage, thereby extending the service life of the material.

[0021] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantages that butyl acetate is used as a solvent to dissolve the mixed monomers and promote the polymerization reaction; the conditions of the polymerization reaction can be accurately controlled by accurately dropping the mixed solution and adding itaconic acid at regular intervals through a micropump, thereby obtaining an acrylic resin with specific properties; stirring and dropping operations are performed under reflux conditions, which is conducive to promoting the mixing and reaction of the reactants and improving the efficiency of the polymerization reaction; 2. The advantages of the present invention are that polyvinyl alcohol fully absorbs water and swells, fully dissolves in water, and forms a uniform solution; the microcapsules prepared by the method have uniform wall material and core material distribution, moderate wall material thickness, high mechanical strength, can effectively protect the core material and control its release, and are suitable for the preparation of a variety of core materials and wall materials. The prepared microcapsules have the advantages of excellent performance, wide application range, environmental protection and energy saving; 3. The present invention has the advantage that the sandpaper performs unidirectional grinding on the magnesium alloy substrate, which is conducive to removing the oxide layer, dirt and uneven parts on the surface of the substrate, making the surface smoother and more uniform, and significantly improving the surface quality of the magnesium alloy substrate. The clean surface is conducive to the close bonding between the coating or treatment layer and the substrate, thereby improving the overall mechanical properties and durability; 4. The present invention has the advantages that by mixing acrylic resin with epoxy resin, n-butanol and xylene are used as solvents to facilitate the dissolution and coating of the resin, and its advantages can be fully utilized to improve the hardness, wear resistance, corrosion resistance and adhesion of the coating; the addition of microcapsules provides the coating with additional functions, such as the release of sustained-release agents, self-repairing ability, etc. 5. The present invention has the advantages of using a constant temperature water bath and a circulating water pump to ensure that the temperature of the plating solution is uniform and stable, thereby improving the stability and repeatability of the electrodeposition process; the iron-nickel alloy coating prepared by electrodeposition has the advantages of good uniformity, low porosity, high density, etc., and using deionized water as a solvent reduces the emission of harmful substances, can reduce energy consumption, and improve production efficiency; 6. The present invention has the advantage that by controlling the PMHS and D4Vi solutions and stirring conditions, a precursor ceramic repair agent matrix with specific properties can be prepared, nano-TiB 2The addition of fillers can significantly improve the hardness, wear resistance and chemical stability of the repair agent, making it more suitable for repair work in various harsh environments; 7. The advantage of adopting the present invention is that the acrylic resin coating provides a basic protective layer for the alloy material, while the repair agent gives the material the ability to self-repair. Heat treatment helps to accelerate the curing process of the acrylic resin coating and make the coating more stable. High-temperature heat treatment allows the repair agent to fully pyrolyze and interact with the electrodeposited iron-nickel alloy to form a corrosion-resistant alloy layer with intelligent self-repair function. When the surface of the material is damaged, the repair agent can respond and repair the damage, thereby extending the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a preparation flow chart of an intelligent self-repairing iron-nickel based corrosion resistant alloy material of the present invention. DETAILED DESCRIPTION

[0023] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0024] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.

[0025] Example 1 Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the inhibitor, then add 1.0g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 15% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.0g of itaconic acid and 4.0g of molecular weight regulator (3-isooctyl mercaptopropionate); put the remaining 75% of the mixed solution into a micro pump for standby use; heat to 100°C, stir under reflux for 0.3h, start to drip the remaining 75% of the mixed solution (drip it in 2h) and add 3.0g of itaconic acid every 0.5h during the dripping process; after the dripping is completed, keep warm for 1h; Step (2) Preparation of microcapsules Soak polyvinyl alcohol and deionized water for 12 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 70°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 40 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; dilute hydrochloric acid with deionized water After that, the aniline was acidified to a pH value of 1; 5% of the acidified aniline was added dropwise to the acrylic resin emulsion and reacted for 1 hour; a light yellow prepolymer emulsion was obtained; at the same time, the remaining 90% of the acidified aniline and the aqueous solution of initiator 2 (ammonium persulfate) were slowly and continuously added dropwise to the four-necked flask, and the addition was completed and reacted for 10 hours; sodium chloride was first used to break the emulsion, deionized water was added, and the solution was filtered using a 0.40 μm filter membrane, washed until the pH was neutral, dispersed in anhydrous ethanol, filtered with a 450-mesh gauze, and the lower layer was removed; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy with a size of 45 mm × 45 mm × 3 mm, and its main components (wt.%) are: Mg, Al 2.5, Si 0.05, Ca 0.03, Zn 0.6, Mn 0.2, Cu 0.01, Ni 0.001; the magnesium alloy substrate is polished in one direction with 150 mesh and 400 mesh sandpaper in turn, and then cleaned with deionized water and anhydrous ethanol and blown dry for standby use, and the 65 mm × 145 mm × 0.45 mm tinplate sheet is cleaned with anhydrous ethanol and blown dry with cold air to obtain the magnesium alloy substrate; Step (4) Preparation of acrylic resin coating Add 2.0% acrylic resin to the epoxy resin (E-44) and stir evenly, then add epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stir, and after fully ripening, apply it on the AZ31B magnesium alloy treated in step (3), and cure it at room temperature for 40 hours and at 50°C for 12 hours to obtain an acrylic resin coating; Step (5) Preparation of Electrodeposited Iron-Nickel Alloy 20g / L nickel sulfate, 15g / L ferrous sulfate, 25g / L sodium chloride, 35g / L boric acid, 15g / L sodium citrate, 1g / L saccharin, 0.2g / L sodium benzene sulfite were placed in different beakers, dissolved with deionized water and poured into the electroforging tank, stirred evenly, started the circulating water pump, stirred the solution at the same time to ensure the uniformity of the plating solution, started the constant temperature water bath, observed the temperature with a thermometer, and ensured that the plating solution temperature was controlled at 55°C; adjusted 1A / dm 2 Pulse current density, fix the electrode, start the power supply to start electrodeposition on the copper foil, and continuously add ferrous sulfate to ensure that Ni in the solution 2+ :Fe 2+ion ratio, the electroplating time is controlled to be 25min; turn off the power and take out the electrodeposited sample; rinse the electrodeposited surface with deionized water and blow dry with a hot air blower; Step (6) Preparation of precursor ceramic repair agent Weigh PMHS and D4Vi solutions, mix them and stir them magnetically at 20°C for 20 min to fully mix the two phases to obtain the matrix of the precursor ceramic repair agent. 2 The filler is added to the repair agent matrix solution, and magnetic stirring is continued for 30 minutes at 24°C to completely mix the polymer repair material and the filler to obtain a precursor ceramic repair agent; Step (7) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish and heat treated by a two-step heat preservation method. The electrodeposited iron-nickel alloy prepared in step (5) is then added and heated to 255°C at a heating rate of 3°C / min in an air environment and then kept warm for 56 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace and heated to 855°C at a heating rate of 2°C / min and kept warm for 62 minutes to fully pyrolyze it, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0026] Example 2 Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the inhibitor, then add 1.2g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 16% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.2g of itaconic acid and 4.2g of molecular weight regulator (3-mercaptopropionate); put the remaining 76% of the mixed solution into a micro pump for standby use; heat to 116°C, stir under reflux for 0.4h, start to drip the remaining 76% of the mixed solution (drip over 4h) and add 3.3g of itaconic acid every 0.6h during the dripping process; after the dripping is completed, keep warm for 2h; Step (2) Preparation of microcapsules Soak polyvinyl alcohol and deionized water for 12 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 72°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 42 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; dilute hydrochloric acid with deionized water After that, the aniline was acidified to a pH value of 1; 6% of the acidified aniline was added dropwise to the acrylic resin emulsion and reacted for 2 hours; a light yellow prepolymer emulsion was obtained; at the same time, the remaining 92% of the acidified aniline and the aqueous solution of initiator 2 (ammonium persulfate) were slowly and continuously added dropwise to the four-necked flask, and the addition was completed and reacted for 11 hours; sodium chloride was first used to break the emulsion, deionized water was added, and the solution was filtered using a 0.42 μm filter membrane, washed until the pH was neutral, dispersed in anhydrous ethanol, filtered with a 455-mesh gauze, and the lower layer was removed; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy of 46mm×46mm×3mm, and its main components (wt.%) are: Mg, Al 3.0, Si 0.06, Ca 0.04, Zn 0.8, Mn 0.5, Cu 0.02, Ni 0.002; the magnesium alloy substrate is polished in one direction with 160 mesh and 420 mesh sandpaper in turn, and then cleaned with deionized water and anhydrous ethanol and blown dry for standby use, and the 66mm×148mm×0.50mm tinplate sheet is cleaned with anhydrous ethanol and blown dry with cold air to obtain the magnesium alloy substrate; Step (4) Preparation of acrylic resin coating Add 3.0% acrylic resin to the epoxy resin (E-44) and stir evenly, then add epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stir, and after fully ripening, apply it on the AZ31B magnesium alloy treated in step (3), and cure it at room temperature for 42 hours and at 52°C for 24 hours to obtain an acrylic resin coating; Step (5) Preparation of Electrodeposited Iron-Nickel Alloy 50g / L nickel sulfate, 16g / L ferrous sulfate, 26g / L sodium chloride, 37g / L boric acid, 18g / L sodium citrate, 2g / L saccharin, 0.3g / L sodium benzene sulfite were placed in different beakers, dissolved with deionized water and poured into the electroforging tank, stirred evenly, started the circulating water pump, stirred the solution at the same time to ensure the uniformity of the plating solution, started the constant temperature water bath, observed the temperature with a thermometer, and ensured that the plating solution temperature was controlled at 56°C; adjusted 2A / dm 2 Pulse current density, fix the electrode, start the power supply to start electrodeposition on the copper foil, and continuously add ferrous sulfate to ensure that Ni in the solution 2+ :Fe 2+ion ratio, the electroplating time is controlled to be 27min; turn off the power and take out the electrodeposited sample; rinse the electrodeposited surface with deionized water and blow dry with a hot air blower; Step (6) Preparation of precursor ceramic repair agent Weigh PMHS and D4Vi solutions, mix them and stir them magnetically at 23°C for 23 minutes to fully mix the two phases to obtain the matrix of the precursor ceramic repair agent. 2 The filler was added into the repair agent matrix solution, and magnetic stirring was continued for 32 minutes at 26°C to completely mix the polymer repair material and the filler to obtain a precursor ceramic repair agent; Step (7) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish, and heat treated by a two-step heat preservation method. Then, the electrodeposited iron-nickel alloy prepared in step (5) is added, and the alloy is heated to 255°C at a heating rate of 6°C / min in an air environment and then kept warm for 56 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace, heated to 860°C at a heating rate of 5°C / min and kept warm for 60 minutes to fully pyrolyze the alloy, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0027] Example 3 Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the inhibitor, then add 1.5g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 20% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.4g of itaconic acid and 4.5g of molecular weight regulator (3-mercaptopropionate); put the remaining 80% of the mixed solution into a micro pump for standby use; heat to 126°C, stir for 0.5h under reflux, start to drip the remaining 80% of the mixed solution (drip over 8h) and add 3.5g of itaconic acid every 1.0h during the dripping process; after the dripping is completed, keep warm for 2h; Step (2) Preparation of microcapsules Soak polyvinyl alcohol and deionized water for 24 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 85°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 45 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; dilute hydrochloric acid with deionized water After that, the aniline was acidified to a pH value of 2; 10% of the acidified aniline was added dropwise to the acrylic resin emulsion and reacted for 3 hours; a light yellow prepolymer emulsion was obtained; at the same time, the remaining 95% of the acidified aniline and the aqueous solution of initiator 2 (ammonium persulfate) were slowly and continuously added dropwise to the four-necked flask, and the addition was completed and reacted for 12 hours; sodium chloride was first used to break the emulsion, deionized water was added, and the solution was filtered using a 0.45 μm filter membrane, washed until the pH was neutral, dispersed in anhydrous ethanol, filtered with a 500-mesh gauze, and the lower layer was removed; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy of 50mm×50mm×5mm, and its main components (wt.%) are: Mg, Al 3.5, Si 0.09, Ca 0.05, Zn 1.4, Mn 1.0, Cu 0.03, Ni 0.004; the magnesium alloy substrate is polished in one direction with 180 mesh and 450 mesh sandpaper in turn, and then cleaned with deionized water and anhydrous ethanol and blown dry. A 65mm×150mm×0.55mm tinplate sheet is prepared, cleaned with anhydrous ethanol, and blown dry with cold air to obtain a magnesium alloy substrate; Step (4) Preparation of acrylic resin coating Add 3.5% of acrylic resin to the epoxy resin (E-44) and stir evenly, then add epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stir, and after fully ripening, apply it on the AZ31B magnesium alloy treated in step (3), and cure it at room temperature for 48 hours and at 55°C for 48 hours to obtain an acrylic resin coating; Step (5) Preparation of Electrodeposited Iron-Nickel Alloy 100g / L nickel sulfate, 20g / L ferrous sulfate, 30g / L sodium chloride, 45g / L boric acid, 15g / L sodium citrate, 4g / L saccharin, 0.3g / L sodium benzene sulfite were placed in different beakers, dissolved with deionized water and poured into the electroforging tank, stirred evenly, started the circulating water pump, stirred the solution at the same time to ensure the uniformity of the plating solution, started the constant temperature water bath, observed the temperature with a thermometer, and ensured that the plating solution temperature was controlled at 60°C; adjusted 8A / dm 2 Pulse current density, fix the electrode, start the power supply to start electrodeposition on the copper foil, and continuously add ferrous sulfate to ensure that Ni in the solution 2+ :Fe 2+ion ratio, the electroplating time is controlled to be 30min; turn off the power and take out the electrodeposited sample; rinse the electrodeposited surface with deionized water and blow dry with a hot air blower; Step (6) Preparation of precursor ceramic repair agent Weigh PMHS and D4Vi solutions, mix them and stir them magnetically at 25°C for 25 minutes to fully mix the two phases to obtain the matrix of the precursor ceramic repair agent. 2 The filler is added to the repair agent matrix solution, and the solution is continuously stirred magnetically for 35 minutes at 30°C to completely mix the polymer repair material and the filler to obtain a precursor ceramic repair agent; Step (7) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish, and heat treated by a two-step heat preservation method. Then, the electrodeposited iron-nickel alloy prepared in step (5) is added, and the alloy is heated to 350°C at a heating rate of 6°C / min in an air environment and then kept warm for 60 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace, heated to 900°C at a heating rate of 5°C / min and kept warm for 65 minutes to fully pyrolyze the alloy, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0028] Example 4 Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the polymerization inhibitor, then add 1.2g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 20% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.4g of itaconic acid and 4.5g of molecular weight regulator (3-mercaptopropionate); put the remaining 80% of the mixed solution into a micro pump for standby use; heat to 126°C, stir for 0.5h under reflux, start to drip the remaining 80% of the mixed solution (drip over 8h) and add 3.2g of itaconic acid every 0.5h during the dripping process; after the dripping is completed, keep warm for 1h; Step (2) Preparation of microcapsules Soak polyvinyl alcohol and deionized water for 24 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 70°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 45 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; dilute hydrochloric acid with deionized water After that, the aniline was acidified to a pH value of 2; 10% of the acidified aniline was added dropwise to the acrylic resin emulsion and reacted for 1 hour; a light yellow prepolymer emulsion was obtained; at the same time, the remaining 90% of the acidified aniline and the aqueous solution of initiator 2 (ammonium persulfate) were slowly and continuously added dropwise to the four-necked flask, and the addition was completed and reacted for 12 hours; sodium chloride was first used to break the emulsion, deionized water was added, and the solution was filtered using a 0.45 μm filter membrane, washed until the pH was neutral, dispersed in anhydrous ethanol, filtered with a 500-mesh gauze, and the lower layer was removed; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy with a size of 50mm×50mm×3mm, and its main components (wt.%) are: Mg, Al 2.5, Si 0.08, Ca 0.04, Zn 0.6, Mn 0.2, Cu 0.01, Ni 0.001; the magnesium alloy substrate is polished in one direction with 180 mesh and 400 mesh sandpaper in turn, and then cleaned with deionized water and anhydrous ethanol and blown dry for use; a 65mm×150mm×0.45mm tinplate sheet is cleaned with anhydrous ethanol and blown dry with cold air to obtain a magnesium alloy substrate.

[0029] Step (4) Preparation of acrylic resin coating 2.5% of acrylic resin was added to the epoxy resin (E-44) and stirred evenly. Then, epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) were added and stirred. After fully ripening, the mixture was coated on the AZ31B magnesium alloy treated in step (3). The mixture was cured at room temperature for 48 hours and at 50°C for 48 hours to obtain an acrylic resin coating.

[0030] Step (5) Preparation of Electrodeposited Iron-Nickel Alloy 100g / L nickel sulfate, 20g / L ferrous sulfate, 30g / L sodium chloride, 40g / L boric acid, 20g / L sodium citrate, 3g / L saccharin, 0.3g / L sodium benzene sulfite were placed in different beakers, dissolved with deionized water and poured into the electroforging tank, stirred evenly, and the solution was stirred to ensure the uniformity of the plating solution. The constant temperature water bath was started, and the temperature was observed by a thermometer to ensure that the plating solution temperature was controlled at 60°C; 4A / dm 2 Pulse current density, fix the electrode, start the power supply to start electrodeposition on the copper foil, and continuously add ferrous sulfate to ensure that Ni in the solution 2+ :Fe2+ ion ratio, the electroplating time is controlled to be 30min; turn off the power and take out the electrodeposited sample; rinse the electrodeposited surface with deionized water and blow dry with a hot air blower; Step (6) Preparation of precursor ceramic repair agent Weigh PMHS and D4Vi solutions, mix them and stir them magnetically at 25°C for 20 min to fully mix the two phases to obtain the matrix of the precursor ceramic repair agent. 2 The filler is added to the repair agent matrix solution, and magnetic stirring is continued for 30 minutes at 25°C to completely mix the polymer repair material and the filler to obtain a precursor ceramic repair agent; Step (7) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish, and heat-treated by a two-step heat preservation method. Then, the electrodeposited iron-nickel alloy prepared in step (5) is added, and the alloy is heated to 260°C at a heating rate of 3°C / min in an air environment and then kept warm for 60 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace, and heated to 900°C at a heating rate of 5°C / min and kept warm for 60 minutes to fully pyrolyze the alloy, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0031] Comparative Example 1 Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the polymerization inhibitor, then add 2.0g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 25% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.5g of itaconic acid and 5.0g of molecular weight regulator (3-mercaptopropionate); put the remaining 75% of the mixed solution into a micro pump for standby use; heat to 130°C, stir under reflux for 1h, start to drip 75% of the mixed solution (drip over 4h) and add 4.0g of itaconic acid every 0.5h during the dripping process; after the dripping is completed, keep warm for 5h; Step (2) Preparation of microcapsules Soak polyvinyl alcohol and deionized water for 48 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 95°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 50 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; dilute hydrochloric acid with deionized water and , acidify aniline to pH 3; add 1510% of the acidified aniline to the acrylic resin emulsion and react for 2 hours; obtain a light yellow prepolymer emulsion; at the same time, slowly and continuously add the remaining 95% of the acidified aniline and the initiator 2 (ammonium persulfate) aqueous solution to the four-necked flask, and react for 15 hours; first use sodium chloride to break the emulsion, add deionized water and filter with a 0.45μm filter membrane, wash until the pH is neutral, disperse in anhydrous ethanol, filter with a 500-mesh gauze, and take the lower layer; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy with a size of 55 mm × 55 mm × 6 mm, and its main components (wt.%) are: Mg, Al 4.5, Si 0.09, Ca 0.06, Zn 1.6, Mn 1.2, Cu 0.05, Ni 0.004; the magnesium alloy substrate is polished in one direction with 180 mesh and 450 mesh sandpaper in sequence, and then cleaned with deionized water and anhydrous ethanol and blown dry for use; the 68 mm × 160 mm × 0.45 mm tinplate sheet is cleaned with anhydrous ethanol and blown dry with cold air to obtain the magnesium alloy substrate; Step (4) Preparation of acrylic resin coating Add 4.5% of acrylic resin to the epoxy resin (E-44) and stir evenly, then add epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stir, and after fully ripening, apply it on the AZ31B magnesium alloy treated in step (3), and cure it at room temperature for 48 hours and at 60°C for 48 hours to obtain an acrylic resin coating; Step (5) Preparation of precursor ceramic repair agent Weigh PMHS and D4Vi solutions, mix them and stir them magnetically at 30°C for 30 min to fully mix the two phases to obtain the matrix of the precursor ceramic repair agent. 2 The filler is added to the repair agent matrix solution, and magnetic stirring is continued at 35°C for 40 minutes to completely mix the polymer repair material and the filler to obtain a precursor ceramic repair agent; Step (6) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (5) are placed in a ceramic dish and heat-treated by a two-step heat preservation method. They are heated to 350°C at a heating rate of 7°C / min in an air environment and then kept warm for 55 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace, heated to 900°C at a heating rate of 4°C / min and kept warm for 65 minutes to fully pyrolyze it, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0032] Comparative Example 2 Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the inhibitor, then add 0.5g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 10% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.2g of itaconic acid and 4.2g of molecular weight regulator (3-mercaptopropionate); put the remaining 65% of the mixed solution into a micro pump for standby use; heat to 100°C, stir under reflux for 0.3h, start to drop the remaining 75% of the mixed solution (drop it in 4h) and add 2.5g of itaconic acid every 1.0h during the drop addition; after the drop addition is completed, keep warm for 0.5h; Step (2) Preparation of microcapsules Soak polyvinyl alcohol and deionized water for 12 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 65°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 35 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; after diluting hydrochloric acid and deionized water, aniline is acidified to a pH value of 1; 5% of the acidified aniline is added dropwise to the acrylic resin emulsion and reacted for 1 hour; a light yellow prepolymer emulsion is obtained; at the same time, the remaining 85% of the acidified aniline and the initiator 2 (ammonium persulfate) aqueous solution are slowly and continuously added dropwise to the four-necked flask, and the addition is completed and the reaction is carried out for 5 hours; first, sodium chloride is used to break the emulsion, deionized water is added, and the mixture is filtered using a 0.30 μm filter membrane, washed until the pH is neutral, dispersed in anhydrous ethanol, filtered with a 400-mesh gauze, and the lower layer is removed; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy of 40mm×40mm×2mm, and its main components (wt.%) are: Mg, Al 2.0, Si 0.03, Ca 0.02, Zn 0.3, Mn 0.2, Cu 0.01, Ni 0.001; the magnesium alloy substrate is polished in one direction with 150 mesh and 400 mesh sandpaper in turn, and then washed with deionized water and anhydrous ethanol and dried for standby use, and the 65mm×145mm×0.45mm tinplate sheet is washed with anhydrous ethanol and dried with cold air to obtain the magnesium alloy substrate; Step (4) Preparation of acrylic resin coating Add 2.0% acrylic resin to the epoxy resin (E-44) and stir evenly, then add epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stir, and after fully ripening, apply it on the AZ31B magnesium alloy treated in step (3), and cure it at room temperature for 35 hours and at 45°C for 12 hours to obtain an acrylic resin coating; Step (5) Preparation of Electrodeposited Iron-Nickel Alloy 25g / L nickel sulfate, 10g / L ferrous sulfate, 20g / L sodium chloride, 35g / L boric acid, 12g / L sodium citrate, 2g / L saccharin, 0.3g / L sodium benzene sulfite were placed in different beakers, dissolved with deionized water and poured into the electroforging tank, stirred evenly, started the circulating water pump, stirred the solution at the same time to ensure the uniformity of the plating solution, started the constant temperature water bath, observed the temperature with a thermometer, and ensured that the plating solution temperature was controlled at 50°C; adjusted 2A / dm 2 Pulse current density, fix the electrode, start the power supply to start electrodeposition on the copper foil, and continuously add ferrous sulfate to ensure that Ni in the solution 2+ :Fe 2+ ion ratio, the electroplating time is controlled to be 20min; turn off the power and take out the electrodeposited sample; rinse the electrodeposited surface with deionized water and blow dry with a hot air blower; Step (6) Intelligent self-repairing iron-nickel based corrosion-resistant alloy material The acrylic resin coating prepared in step (4) is placed in a ceramic dish and heat-treated by a two-step heat preservation method. The electrodeposited iron-nickel alloy prepared in step (5) is then added and heated to 200°C at a heating rate of 2°C / min in an air environment and then kept warm for 50 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace and heated to 800°C at a heating rate of 4°C / min and kept warm for 55 minutes to fully pyrolyze it, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

[0033] Comparison of detection experiments: The intelligent self-repairing iron-nickel-based corrosion-resistant alloy materials obtained in Examples 1 to 4 and comparative products 1 and 2 were tested, and the specific testing method is as follows: Corrosion resistance test The Tafel polarization curve of the alloy was tested using an electrochemical workstation to evaluate its corrosion resistance. A 3.5% NaCl solution was used, that is, 3.63 g of NaCl was added to every 100 ml of water. After each sample was tested, the solution was replaced, and 100 ml of solution was used each time.

[0034] Self-healing performance test By artificially creating damage (such as scratches, cracks, etc.), the self-healing ability of the alloy under specific conditions is observed. Use a knife to create scratches on the surface of the material. The depth and width of the scratches or notches should be determined according to the thickness of the material and the expected self-healing ability; the scratch depth can be 0.1mm-1mm and the width can be 0.2mm-2mm; the length and width of the crack should also be set according to the brittleness and toughness of the material. Usually, the crack length does not exceed 10% of the material length.

[0035] Wear resistance test Friction and wear test: By simulating the friction conditions encountered by the material during use, such as using a friction and wear tester to test, the wear resistance of the material is evaluated. The material is a polymer material, the load range is set to 10N to 100N; the sliding friction speed is set to 200r / min or 400r / min, and the test time can be set to 1-2 hours.

[0036] Table 1 Corrosion resistance test

[0037] As can be seen from Table 1, Example 4 is the best, while Comparative Example 1 is relatively poor. In the pretreatment of the magnesium alloy substrate in Example 4, the magnesium alloy substrate is carefully polished and cleaned to ensure the flatness and cleanliness of the substrate surface. This helps to closely bond the coating to the substrate, improve the adhesion and corrosion resistance of the coating; the preparation of the electrodeposited iron-nickel alloy ensures the uniformity and density of the alloy layer, which helps to improve the corrosion resistance of the alloy layer; in comparison, Comparative Example 1 has certain deficiencies and differences in these aspects, resulting in its relatively poor corrosion resistance.

[0038] Table 2 Self-repair performance test

[0039] As can be seen from Table 2, Example 4 is the best and Comparative Example 1 is poor. In Example 4, a two-step heat treatment method with insulation is adopted, which helps to accelerate the curing process and fully pyrolyze the material, thereby improving the overall performance and self-healing performance of the material; at the same time, a two-step heat treatment method with insulation is adopted, which helps to accelerate the curing process and fully pyrolyze the material, thereby improving the overall performance and self-healing performance of the material. In Comparative Example 1, due to the differences in the previous steps and the different heat treatment conditions, the performance of the final material is not as good as that of Example 4.

[0040] Table 3 Wear resistance test

[0041] As shown in Table 3, Example 4 is the best and Comparative Example 2 is the worst. The acrylic resin in Example 4 has a higher crosslinking density and a more stable structure, thereby improving its wear resistance. The extension of the emulsification time for the preparation of microcapsules and the increase of acidified aniline make the microcapsules better dispersed and fixed in the resin coating, further improving the wear resistance. The acrylic resin coating uses more acrylic resin and a longer curing time, which is conducive to having a stronger coating, thereby improving the wear resistance.

[0042] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. Preparation of an intelligent self-repairing iron-nickel based corrosion resistant alloy material, characterized in that: include: Step (1) synthesis of acrylic resin, step (2) preparation process of microcapsules, step (3) pretreatment of magnesium alloy substrate, step (4) preparation of acrylic resin coating, step (5) preparation of electrodeposited iron-nickel alloy, step (6) preparation of precursor ceramic repair agent, step (7) intelligent self-repairing iron-nickel based corrosion resistant alloy material; Wherein, the preparation of the precursor ceramic repair agent in step (6) comprises: Weigh PMHS (polymethyl hydrogen siloxane) and D4Vi solution (acrylate copolymer emulsion), mix them and stir them magnetically to fully mix the two-phase solution to obtain the matrix part of the precursor ceramic repair agent; on the basis of the precursor repair agent matrix, weigh nano-TiB2 filler and add it to the repair agent matrix solution, continue to stir to make the polymer repair material and the filler completely mixed to obtain the precursor ceramic repair agent; Step (7) The intelligent self-repairing iron-nickel based corrosion resistant alloy material comprises: The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are heat-treated by a two-step heat preservation method, and then the electrodeposited iron-nickel alloy prepared in step (5) is added, and the temperature is increased in an air environment and then kept warm to accelerate the curing process. The completely cured material is heated and kept warm to fully pyrolyze it, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

2. The preparation of the intelligent self-repairing iron-nickel based corrosion resistant alloy material according to claim 1 is characterized in that: Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the polymerization inhibitor, then add initiator 1 (dibenzoyl peroxide and dibutyl phthalate) to mix; take the mixed solution and butyl acetate and mix them into a four-necked flask, then add itaconic acid and a molecular weight regulator (3-mercaptopropionate); put the remaining mixed solution into a micro pump for standby use; stir under heating and reflux conditions, start to drop the mixed solution and add itaconic acid during the dropping process; after the dropping is completed, keep warm; Step (2) Preparation of microcapsules Soak polyvinyl alcohol in deionized water and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature; finally obtain a stable acrylic resin emulsion, which is milky white in color; dilute hydrochloric acid with deionized water, acidify aniline to a certain pH range, and drop the acidified aniline into the acrylic resin emulsion to react, thereby obtaining a light yellow prepolymer emulsion; at the same time, slowly and continuously drop the acidified aniline and initiator 2 (ammonium persulfate) aqueous solution into a four-necked flask until the addition is complete; first use sodium chloride to break the emulsion, add deionized water and use a filter membrane to filter, wash until the pH is neutral, disperse in anhydrous ethanol, filter with gauze, and remove the lower layer; Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy, whose main components are: Mg, Al, Si, Ca, Zn, Mn, Cu, Ni; the magnesium alloy substrate is polished in one direction with sandpaper, then cleaned with deionized water and anhydrous ethanol and blown dry for standby use, cleaned with anhydrous ethanol, and blown dry with cold air to obtain the magnesium alloy substrate; Step (4) Preparation of acrylic resin coating Adding acrylic resin to epoxy resin (E-44) and stirring evenly, then adding epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stirring, coating on the AZ31B magnesium alloy treated in step (3) after fully ripening, and curing at room temperature to obtain an acrylic resin coating; Step (5) Preparation of Electrodeposited Iron-Nickel Alloy Nickel sulfate, ferrous sulfate, sodium chloride, boric acid, sodium citrate, saccharin, and sodium benzenesulfite are placed in different beakers, dissolved in deionized water, and poured into an electric forging tank, stirred evenly, and a circulating water pump is started. The solution is stirred to ensure the uniformity of the plating solution, and a constant temperature water bath is started. The temperature is observed by a thermometer, the current density is adjusted, the electrodes are fixed, and the power is started to start electrodeposition on the copper foil. At the same time, ferrous sulfate is continuously added to ensure the ion ratio in the solution and the electroplating time is controlled; the power is turned off and the electrodeposited sample is taken out; the electrodeposited surface is rinsed with deionized water and blown dry with a hot air blower; Step (6) Preparation of precursor ceramic repair agent Weigh PMHS (polymethyl hydrogen siloxane) and D4Vi solution (acrylate copolymer emulsion), mix them and stir them magnetically to fully mix the two-phase solution to obtain the matrix part of the precursor ceramic repair agent; on the basis of the precursor repair agent matrix, weigh nano-TiB2 filler and add it to the repair agent matrix solution, continue to stir to make the polymer repair material and the filler completely mixed to obtain the precursor ceramic repair agent; Step (7) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish, and heat-treated by a two-step heat preservation method. Then, the electrodeposited iron-nickel alloy prepared in step (5) is added, and the temperature is increased in an air environment and then kept warm to accelerate the curing process. The completely cured material is placed in a muffle furnace, heated and kept warm to fully pyrolyze it, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

3. The preparation of an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material according to claim 2, characterized in that: Step (1) Synthesis of acrylic resin After mixing methyl methacrylate, butyl methacrylate and butyl acrylate, use NaOH to remove the inhibitor, then add 1.0-1.5g of initiator 1 (dibenzoyl peroxide and dibutyl phthalate); take 15-20% of the mixed solution and mix it with butyl acetate and pour it into a four-necked flask, then add 6.0-6.4g of itaconic acid and 4.0-4.5g of molecular weight regulator (3-isooctyl mercaptopropionate); the remaining 75-80% of the mixed solution is put into a micro pump for standby use; heat to 100-126°C, stir for 0.3-0.5h under reflux condition, start to drip the remaining 75-80% of the mixed solution (drip in 2-8h) and add 3.0-3.5g of itaconic acid every 0.5-1.0h during the dripping process; after the dripping is completed, keep warm for 1-2h.

4. The preparation of an intelligent self-repairing iron-nickel based corrosion resistant alloy material according to claim 3, characterized in that: Step (2) Preparation of microcapsules Soak polyvinyl alcohol and deionized water for 12-24 hours, and then stir until a colorless and transparent jelly is obtained; add deionized water to the polyvinyl alcohol jelly and dissolve it at 70-85°C; add emulsifier polyvinyl pyrrolidone, polyvinyl alcohol jelly solution and acrylic resin prepared in step (1) into a three-necked flask equipped with an electric stirrer, stir until completely mixed, and emulsify at room temperature for 40-45 minutes; finally, a stable acrylic resin emulsion is obtained, and the emulsion color is milky white; dilute hydrochloric acid with deionized water, and add aniline acid to pH 1-2; add 5-10% of acidified aniline to the acrylic resin emulsion and react for 1-3h; obtain a light yellow prepolymer emulsion; at the same time, slowly and continuously add the remaining 90-95% of acidified aniline and initiator 2 (ammonium persulfate) aqueous solution to the four-necked flask, and react for 10-12h after the addition is complete; first use sodium chloride to break the emulsion, add deionized water and filter with a 0.40-0.45μm filter membrane, wash until the pH is neutral, disperse in anhydrous ethanol, filter with 450-500 mesh gauze, and remove the lower layer.

5. The preparation of an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material according to claim 2, characterized in that: Step (3) Pretreatment of magnesium alloy substrate The experimental substrate is AZ31B magnesium alloy with a size of 45-50mm×45-50mm×3-5mm, and its main components (wt.%) are: Mg, Al2.5-3.5, Si 0.05-0.09, Ca 0.03-0.05, Zn 0.6-1.4, Mn 0.2-1.0, Cu 0.01-0.03, Ni0.001-0.004; the magnesium alloy substrate is polished in one direction with 150-180 mesh and 400-450 mesh sandpaper in turn, and then cleaned with deionized water and anhydrous ethanol and blown dry for use, and the tinplate sheet with a size of 65-68mm×145-150mm×0.45-0.55mm is cleaned with anhydrous ethanol and blown dry with cold air to obtain the magnesium alloy substrate.

6. The preparation of an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material according to claim 5, characterized in that: Step (4) Preparation of acrylic resin coating Add 2.0-3.5% of acrylic resin to the epoxy resin (E-44) and stir evenly, then add epoxy resin curing agent 2015, n-butanol and xylene, and the microcapsules prepared in step (2) and stir, and after fully ripening, apply it on the AZ31B magnesium alloy treated in step (3), and cure it at room temperature for 40-48 hours and at 50-55°C for 12-48 hours to obtain an acrylic resin coating.

7. The preparation of an intelligent self-repairing iron-nickel based corrosion resistant alloy material according to claim 2, characterized in that: Step (5) Preparation of Electrodeposited Iron-Nickel Alloy Place 20-120g / L nickel sulfate, 15-20g / L ferrous sulfate, 25-30g / L sodium chloride, 35-45g / L boric acid, 15-22g / L sodium citrate, 1-4g / L saccharin, and 0.2-0.5g / L sodium benzene sulfite in different beakers, dissolve them in deionized water, and pour them into the electric forging tank, stir evenly, start the circulating water pump, stir the solution at the same time to ensure the uniformity of the plating solution, start the constant temperature water bath, observe the temperature through the thermometer, and ensure that the plating solution temperature is controlled at 55-60°C; adjust 1-8A / dm 2 Pulse current density, fix the electrode, start the power supply to start electrodeposition on the copper foil, and continuously add ferrous sulfate to ensure that Ni in the solution 2+ :Fe 2+ ion ratio, the electroplating time is controlled to be 25-30min; turn off the power and take out the electrodeposited sample; rinse the electrodeposited surface with deionized water and blow dry with a hot air blower.

8. The preparation of an intelligent self-repairing iron-nickel based corrosion resistant alloy material according to claim 2, characterized in that: Step (6) Preparation of precursor ceramic repair agent Weigh PMHS and D4Vi solutions, mix them, and then magnetically stir them at 20-25°C for 20-25 minutes to fully mix the two-phase solution to obtain the matrix part of the precursor ceramic repair agent; on the basis of the precursor repair agent matrix, weigh nano-TiB2 filler and add it to the repair agent matrix solution, and continue to magnetically stir for 30-35 minutes at 24-30°C to completely mix the polymer repair material and the filler to obtain the precursor ceramic repair agent.

9. The preparation of an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material according to claim 8, characterized in that: Step (7) Intelligent self-repairing iron-nickel based corrosion resistant alloy material The acrylic resin coating prepared in step (4) and the repair agent prepared in step (6) are placed in a ceramic dish, and heat-treated by a two-step heat preservation method. Then, the electrodeposited iron-nickel alloy prepared in step (5) is added, and the alloy is heated to 250-350°C at a heating rate of 3-6°C / min in an air environment, and then kept warm for 55-60 minutes to accelerate the curing process. The completely cured material is placed in a muffle furnace, and heated to 850-900°C at a heating rate of 1-5°C / min and kept warm for 60-65 minutes to fully pyrolyze the alloy, thereby obtaining an intelligent self-repairing iron-nickel-based corrosion-resistant alloy material.

Citation Information

Cited By

  • Collagen anticorrosive coating with tissue repair performance, preparation method and application

    CN122075810A